Macroanatomical study on origin and distribution of Caucasian Lynx (Lynx lynx dinniki)’s the brachial plexus - Takcı, Lutfi; Arı, Hasan Hüseyin (Universidad del Zulia p-ISSN 0798-2259; e-ISSN 2521-9715; l-ISSN 2477-944X, 2025)
This study aimed to determine the formation of the plexus brachialis, the nerves that ramify from the plexus, and their last branches in the Caucasian Lynx. It was found that the formation of the brachial plexus contributed to the ventral branches of the C6th, C7th, C8th, and T1th spinal nerves in the lynx. The ventral root of the C6th spinal nerve gave rise to the suprascapular nerve, the ventral of the C6th and C7th spinal nerve to the subscapular nerves and musculocutaneous nerve, the C7th to the cranial pectoral nerve, the C8th to the caudal pectoral nerve, the C8th and T1th to the lateral pectoral nerve, the radial nerve and the ulnar nerve, and the C7th, C8th, and T1th to the median nerve. The network formed by these branches was the origin of the cranial, caudal, long and lateral pectoral nerves, the suprascapular nerve to the extrinsic muscles of the scapula, the subscapular nerve to the intrinsic muscle of the scapula, the axillary nerve to the major teres and caudal portion of the subscapular muscle, the musculocutaneous nerve to the biceps muscle and its cutaneous, the radial nerve to the muscles of the forearm and pawn craniolateral aspect, the median nerve to the flexor digitorium superficial and profound muscles, and the ulnar nerve to the flexor ulnar carpi and the flexor deep digitorium muscle. Este estudio tuvo como objetivo determinar la formación del plexus brachialis, los nervios que se ramifican del plexo y sus últimas ramificaciones en el Lince del Cáucaso. Se encontró que en la formación del plexo braquial contribuyeron las ramas ventrales de los nervios espinales C6, C7, C8 y T1 en el lince. La raíz ventral del nervio espinal C6 dio origen al nervio supraescapular, la ventral de los nervios espinales C6 y C7 a los nervios subescapulares y al nervio musculocutáneo, el C7 al nervio pectoral craneal, el C8 al nervio pectoral caudal, el C8 y T1 al nervio pectoral lateral, al nervio radial y al nervio ulnar, y el C7, C8 y T1 al nervio mediano. La red formada por estas ramas fue el origen de ...